Asymmetric Organocatalytic Aza-Michael Reactions of Isatin Derivatives - Žari, Sergei; Metsala, Andrus; Kudrjashova, Marina; Kaabel, Sandra; Järving, Ivar; Kanger, Tõnis (Synthesis, 2015)
Isatin was activated by derivatization to a Schiff base with aniline and used as an aza-Michael donor in organocatalytic asymmetric reactions with symmetric and nonsymmetric unsaturated 1,4-diketones. After hydrolysis (in situ), the N-substituted isatins were obtained in high yields (up to >95%) with high enantioselectivity (up to 95%).
Keywords: Michael addition; asymmetric catalysis; enantioselectivity; chemoselectivity; imines